Intersectionality, Measurement, Methods, and Translation: Reflflections on the 2023 AAHB Conference - David Seal; Annie Nguyen; Lisa Benz Scott; Scott Rhodes (New Prairie Press, 2023)
Intersectionality is a critical yet understudied and often misused concept in health behavior research. To address this, the American Academy of Health Behavior organized its 2023 annual scientific conference held on March 12-15th, 2023 around issues of intersectionality conceptualization, measurement, and methods (San Francisco, California). The conference, titled "The science of identities: Measurement & methods for translational health behavior research," brought together a diverse group of nearly 170 health behavior researchers from across the United States to highlight current research and challenges facing intersectionality. The conference included two invited keynotes and eight symposium presentations. Here, we highlight some of the research presented and key themes that emerged across presentations.